Multirotor UAV-Based Photogrammetric Mapping for Road Design - Muhammad Akmal Zulkipli; Khairul Nizam Tahar (International Journal of Optics)
Unmanned Aerial Vehicles (UAVs) can be used for close range mapping. In engineering survey works, the conventional survey involves huge cost, labour, and time. Low-cost UAVs are very practical in providing reliable information for many applications such as road design. UAVs can provide the output that meets the accuracy of engineering surveys and policies, especially for small-scale mapping. UAVs are also a competitive technology which is stable and rapidly developing, same as other surveying technologies. This study investigates the performance of multirotor UAV for road design. This study involves four phases which consist of preliminary study, data collection, data processing, and analysis. This study focuses on the UAV as a tool to capture data of the ground from a certain altitude. The analysis includes UAV flight planning, image acquisition, and accuracy assessment of road design. It can be concluded that UAVs can be used to provide data for road design with reliable accuracy.